FAKTOR FAKTOR KUALITAS LAYANAN NASABAH PADA PT. BANK KALBAR CABANG UTAMA PONTIANAK - B31106099, Iwan Hafidz Setiawan (Jurnal Manajemen Update, 2012)
Quality of services provided by the bank will determine the success of the company's strategy. Clients expect their needs to be served in a fast, responsive, safe, comfortable and efficient as well as get a good and polite behavior of the banks. Hope is not something that is excessive given the customer feel has contributed to the bank, so natural that customers expect excellent service from the bank as a commitment from the bank that the existence of these clients always get attention and retained. Clients who are considered to be loyal to the bank, and by itself would make the purchase of the products offered by banks with high commitment within the lama.Hal This is why the quality of performance in banking services is a very necessary to get attention serious to support and expedite transactions in financial Under these conditions, this paper theoretically intended to provide a view towards improving the quality of service so as to satisfy the customer. This has been discussed in the literature, various concepts of service strategy and various supporting factors. The purpose of this paper is to determine how the responses of the respondents to the quality of service and how customer satisfaction PT. Bank Kalbar The research method used was in the form of a survey conducted through observation, kusioner, interviews and documentary studies. Sampling was done by purposive sampling method of 100 respondents drawn from the whole number of customers at PT. Bank Kalimantan Barat. Data analysis method used is qualitative By collecting data and information from kusioner answered by respondents, who then answers are tabulated and presented in a tabular format and analyzed in accordance with the purpose of the study by using a percentage The conclusions obtained in this study is that the services provided by PT. Bank Main Branch Pontianak Kalimantan is quite optimal, but hopefully there is still perbaikkan quality service in providing financial services and also pay attention to human resources to be more professional Keywords: Quality of customer service